2015
DOI: 10.7554/elife.06085
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar associative sensory learning defects in five mouse autism models

Abstract: Sensory integration difficulties have been reported in autism, but their underlying brain-circuit mechanisms are underexplored. Using five autism-related mouse models, Shank3+/ΔC, Mecp2R308/Y, Cntnap2−/−, L7-Tsc1 (L7/Pcp2Cre::Tsc1flox/+), and patDp(15q11-13)/+, we report specific perturbations in delay eyeblink conditioning, a form of associative sensory learning requiring cerebellar plasticity. By distinguishing perturbations in the probability and characteristics of learned responses, we found that probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 116 publications
7
160
0
1
Order By: Relevance
“…In fact, we have demonstrated that many models of neurodevelopmental syndromes associated with ASD demonstrate abnormalities in cerebellar associative learning with abnormal eye-blink conditioning in mouse models with mutations in mecp2, shank3, cntnap2, or tsc1, or paternal 15q11-13 duplication [39]. Further evidence of a cerebellar contribution to ASD are discussed here in these monogenic neurodevelopmental disorders associated with high rates of ASD.…”
Section: Evidence From Neurodevelopmental Disordersmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, we have demonstrated that many models of neurodevelopmental syndromes associated with ASD demonstrate abnormalities in cerebellar associative learning with abnormal eye-blink conditioning in mouse models with mutations in mecp2, shank3, cntnap2, or tsc1, or paternal 15q11-13 duplication [39]. Further evidence of a cerebellar contribution to ASD are discussed here in these monogenic neurodevelopmental disorders associated with high rates of ASD.…”
Section: Evidence From Neurodevelopmental Disordersmentioning
confidence: 90%
“…Moreover, ASD in TSC correlates with the presence of cerebellar lesions, whereas abnormal deep cerebellar nuclei function has been identified in patients with ASD and TSC [33,60]. In addition, we have demonstrated that mouse models of TSC display impairments in cerebellar eye-blink conditioning paradigms, further supporting roles for cerebellar dysfunction in the pathogenesis of ASD [39].…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 93%
See 1 more Smart Citation
“…Cntnap2-null mice showed normal sensory responsiveness, gross motor function, and noncerebellar learning and memory functioning, but conditional responses and cerebellum-based learning were significantly reduced [Kloth et al, 2015]. In addition, they showed sig-nificant deficits in working and reference memory during acquisition of a task, while Cntnap2-null mice performed comparably to wild-type mice during the retention period [Rendall et al, 2016].…”
Section: Phenotypes Of Cntnap2-null Micementioning
confidence: 98%
“…Studies of learning behavior and auditory processing in Cntnap2-null mice have generated novel insights relevant to ASD and other neurodevelopmental disorders [Kloth et al, 2015;Truong et al, 2015;Rendall et al, 2016]. These transgenic mice showed reduced silent gap detection but superior pitch-related discrimination as compared to wild-type controls.…”
Section: Phenotypes Of Cntnap2-null Micementioning
confidence: 99%